EFFECT OF HESPERETIN TREATMENT ON BLOOD GLUCOSE LEVEL, SPERMATOZOA QUALITY, AND SPERMATOZOA QUANTITY IN ALLOXAN-INDUCED DIABETIC MICE - Nerdy Nerdy; Linta Meliala; Bunga Rimta Barus; Puji Lestari; Selamat Ginting; Peny Ariani; Vriezka Mierza; Tedy Kurniawan Bakri (Jurnal Kedokteran Hewan, 2021)
Male infertility has occurred rapidly in the last few decades, primarily in developing countries. An antioxidant, hesperetin is a flavonoid that is found in abundance in orange peels. The aims of this research were to determine the effect of hesperetin on blood sugar levels, spermatozoaquality, and spermatozoa quantity. The research structure included induction of diabetes mellitus and treatment for 8 weeks, followed bydetermination of blood sugar levels, spermatozoa quality, and spermatozoa quantity. Hesperetin has the ability to restore blood sugar levels, spermatozoa quantity, seminiferous tubules diameter, and testicular weight, volume, and germinal epithelial layer thickness with significant difference from the normal control group. Hesperetin did not fully restore spermatozoa motility, viability, and morphology with significant difference from the normal control group, nor from the positive control group. However, overall, hesperetin decreased blood glucose levels, increased spermatozoa quantity, and improved the spermatozoa quality in alloxan-induced diabetes mellitus mice. Dose-dependent activity was observed with the optimum dose at 200 mg/kg body weight.